THE EFFECT OF SERVICE QUALITY ON COMMUNITY SATISFACTION IN TLOGOSARI DISTRICT - Diana Puspita Sari; Supardi -; Yuniorita Indah Handayani (STIE Mandala Jember, 2022)
The purpose of this study was to examine and analyze the effects of partially and simultaneouslythe dimensions of service quality consisting of reliability, responsiveness, assurance, empathyand physical evidence on community satisfaction in Tlogosari District, Bondowoso Regency.This study uses a survey research form with a questionnaire as a data collection tool which isdistributed to 75 (respondents) communities in Tlogosari District by selecting samples byaccidental sampling. Testing is carried out using validity and reliability tests. Data processingwas analyzed using descriptive statistics with multiple linear regression analysis techniquesusing SPSS 22.0. Based on the results of the study, it was concluded that there was a significantinfluence between reliability, responsiveness of empathy and physical evidence on thesatisfaction of the people of Tlogosari District, while guarantee had no significant effect on thesatisfaction of the people of Tlogosari District. Simultaneously all dimensions of service qualityhave a significant effect on community satisfaction in Tlogosari District.Keywords: service quality, community satisfaction, subdistrict